The Potato Yam Phyllosphere Ectosymbiont Paraburkholderia sp. Msb3 Is a Potent Growth Promotor in Tomato - Herpell, Johannes B.; Schindler, Florian; Bejtović, Mersad; Fragner, Lena; Diallo, Bocar; Bellaire, Anke; Kublik, Susanne; Foesel, Bärbel U.; Gschwendtner, Silvia; Kerou, Melina; Schloter, Michael; Weckwerth, Wolfram (Frontiers in Microbiology, 2020)
The genus Paraburkholderia includes a variety of species with promising features for sustainable biotechnological solutions in agriculture through increasing crop productivity. Here we present a novel Paraburkholderia isolate, a permanent and predominant member of the Dioscoreae bulbifera (yam family, Dioscoreaceae) phyllosphere, making up to 25% of the microbial community on leaf acumens. The 8.5 Mbp genome of isolate Msb3 encodes an unprecedented combination of features mediating a beneficial plant-associated lifestyle, including biological nitrogen fixation (BNF), plant hormone regulation, detoxification of various xenobiotics, degradation of aromatic compounds and multiple protein secretion systems including both T3SS and T6SS. The isolate exhibits significant growth promotion when applied to agriculturally important plants such as tomato, by increasing the total dry biomass by up to 40%. The open question about the ‘beneficial’ nature of this strain led us to investigate ecological and generic boundaries in Burkholderia sensu lato. In a refined phylogeny including 279 Burkholderia sensu lato isolates strain Msb3 clusters within Clade I Paraburkholderia, which also includes few opportunistic strains that can potentially act as pathogens, as revealed by our ecological meta-data analysis. In fact, we demonstrate that all genera originating from the ‘plant beneficial and environmental’ (PBE) Burkholderia species cluster include opportunists. This indicates that further functional examinations are needed before safe application of these strains in sustainable agricultural settings can be assured.